Associations between tertiary lymphoid structure density and immune checkpoint inhibitor efficacy in solid tumors: systematic review and meta-analysis - Jiang, Bin; Wu, Zhuo; Zhang, Yang; Yang, Xueying (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLS) play a crucial role in tumor immunity, yet their relationship with the efficacy of immune checkpoint inhibitors (ICI) in cancer therapy is not fully understood. This study aims to systematically evaluate how TLS density influences treatment outcomes in cancer patients receiving ICI therapy.The PubMed, Embase, Cochrane Library, and Web of Science databases were searched for eligible studies published before January 22, 2024. Our analysis encompassed odds ratios (ORs) for response rates (RRs) and hazard ratios (HRs) for progression-free survival (PFS), each with their respective 95% confidence intervals (CIs).Our meta-analysis, including 19 clinical trials with 1,752 patients, identified a strong correlation between high TLS density and increased RR to ICIs (OR= 2.99, 95% CI: 2.14-4.18, P < 0.001). Furthermore, a higher TLS density was associated with prolonged PFS (HR=0.75, 95% CI: 0.63-0.88, P < 0.001). Specifically, in the context of non-small cell lung cancer (NSCLC), breast cancer (BC), renal cell carcinoma (RCC), esophageal cancer (EC), and urothelial carcinoma (UC), a significant relationship was observed between high TLS density and better ICI efficacy. Publication bias did not affect the integrity of our conclusions. Sensitivity analysis further reinforced the reliability of our aggregated outcomes.Our meta-analysis underscores the predictive role of TLS density in determining the RR and PFS among cancer patients undergoing ICI therapy. These results highlight the prognostic significance of TLS, suggesting its potential as a biomarker for guiding treatment decisions, even in tumor types traditionally considered ICI-resistant.Clinicians are recommended to assess TLS density as a part of patient evaluation to optimize ICI therapy initiation.